Transcriptome-enabled discovery and functional characterization of enzymes related to (2S)-pinocembrin biosynthesis from Ornithogalum caudatum and their application for metabolic engineering. Issue 1 (December 2016) - Guo, Lei; Chen, Xi; Li, Li-Na; Tang, Wei; Pan, Yi-Ting; Kong, Jian-Qiang
Abstract Background (2S )-Pinocembrin is a chiral flavanone with versatile pharmacological and biological activities. Its health-promoting effects have spurred on research effects on the microbial production of (2S )-pinocembrin. However, an often-overlooked salient feature in the analysis of microbial (2S )-pinocembrin is its chirality. Results Here, we presented a full characterization of absolute configuration of microbial (2S )-pinocembrin from engineeredEscherichia coli . Specifically, a transcriptome-wide search for genes related to (2S )-pinocembrin biosynthesis fromOrnithogalum caudatum, a plant rich in flavonoids, was first performed in the present study. A total of 104, 180 unigenes were finally generated with an average length of 520 bp. The Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway mapping assigned 26 unigenes, representing three enzyme families of 4-coumarate:coenzyme A ligase (4CL), chalcone synthase (CHS) and chalcone isomerase(CHI), onto (2S )-pinocembrin biosynthetic pathway. A total of seven, three and one full-length candidates encoding 4CL, CHS and CHI were then verified by reverse transcription polymerase chain reaction, respectively. These candidates were screened by functional expression inE. coli individual or coupled multienzyme reaction systems based on metabolic engineering processes.Oc4CL1, OcCHS2 andOcCHI were identified to bebona fide genes encoding respective pathway enzymes of (2S )-pinocembrin biosynthesis. ThenOc4CL1, OcCHS2 andMsCHI fromMedicago sativa, assembled as artificial gene clusters in different organizations, were used for fermentation production of (2S )-pinocembrin inE. coli . The absolute configuration of the resulting microbial pinocembrin at C-2 was assigned to be2S -configured by combination of retention time, UV spectrum, LC–MS, NMR, optical rotation and circular dichroism spectroscopy. Improvement of (2S )-pinocembrin titres was then achieved by optimization of gene organizations, using of codon-optimized pathway enzymes and addition of cerulenin for increasing intracellular malonyl CoA pools. Overall, the optimized strain can produce (2S )-pinocembrin of 36.92 ± 4.1 mg/L. Conclusions High titre of (2S )-pinocembrin can be obtained from engineeredE. coli by an efficient method. The fermentative production of microbial (2S )-pinocembrin inE. coli paved the way for yield improvement and further pharmacological testing.